Protective effects of xanthohumol against the genotoxicity of heterocyclic aromatic amines MeIQx and PhIP in bacteria and in human hepatoma (HepG2) cells - Olga Viegas (2012)
Previous studies showed that xanthohumol (XN), a hop derived prenylflavonoid, very efficiently protects against genotoxicity and potential carcinogenicity of the food borne carcinogenic heterocyclic aromatic amine (HAA) 2-amino-3-methylimidazo[4,5-f]quinoline (IQ). In this study, we showed that XN was not mutagenic in Salmonella typhimurium TA98 and did not induce genomic instability in human hepatoma HepG2 cells. In the bacteria XN suppressed the formation of 2-amino-1-methyl-6-phenylimidazo[4, 5-b]pyridine (PhIP) and 2-amino-3,8 dimethylimidazo[4,5-f]quinoxaline (MeIQx) induced mutations in a dose dependent manner and in HepG2 cells it completely prevented PhIP and MeIQx induced DNA strand breaks at nanomolar concentrations. With the QRT-PCR gene expression analysis of the main enzymes involved in the biotransformation of HAAs in HepG2 cells we found that XN upregulates the expression of phase I (CYP1A1 and CYP1A2) and phase II (UGT1A1) enzymes. Further gene expression analysis in cells exposed to MeIQx and PhIP in combination with XN revealed that XN mediated up-regulation of UGT1A1 expression may be important mechanism of XN mediated protection against HAAs induced genotoxicity. Our findings confirm the evidence that XN displays strong chemopreventive effects against genotoxicity of HAAs, and provides additional mechanistic information to assess its potential chemopreventive efficiency in humans.